(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
In recent years, far-right populism has gained prominence in Latin America, intensifying anti-democratic rhetoric in countries like Brazil and Argentina. Both Jair Bolsonaro and Javier Milei employed similar discourses, questioning electoral legitimacy and promoting authoritarian interventions. This article analyzes the role of traditional media in legitimizing such rhetoric on social media platforms, examining how major newspapers present Bolsonaro and Milei’s discourses in Facebook posts. Using a dataset from La Nación, Clarín, Estadão, and Folha de S.Paulo, the study explores how far-right populism is framed, circulated, and engaged with audiences during the second rounds of elections in Brazil and Argentina.